Albania : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Albania. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights that Albania's economy continues to strengthen, benefitting from rising domestic demand, large energy-related foreign direct investment (FDI), and a recovery in key European Union (EU) trading partners. The declining output gap and pass-through of higher external inflation have pushed up inflation to just under 2 percent. Short-term external vulnerabilities are limited, as the current account deficit is predominantly funded by concessional borrowing and large FDI inflows, while official foreign reserves are ample. The medium-term outlook remains favorable. GDP growth is projected to accelerate to about 4 percent, driven by continued strong domestic demand, reforms that improve the business climate, and a strengthening EU recovery.